ChemInform Abstract: Synthesis and Characterization of the Rubidium Thiophosphate Rb6(PS5)(P2P10) and the Rubidium Silver Thiophosphates Rb2AgPS4, RbAg5(PS4)2 and Rb3Ag9(PS4)4. Issue 21 (6th May 2016) - Alahmari, Fatimah; Davaasuren, Bambar; Khanderi, Jayaprakash; Rothenberger, Alexander
Abstract: The title compounds are characterized by single crystal XRD, Raman spectroscopy, and UV/VIS diffuse reflectance measurements.